2012
DOI: 10.1074/jbc.m112.412635
|View full text |Cite
|
Sign up to set email alerts
|

Isozyme-specific Interaction of Protein Kinase Cδ with Mitochondria Dissected Using Live Cell Fluorescence Imaging

Abstract: Background: PKC␦ signaling to mitochondria affects cellular apoptosis and metabolism. Results: A structure-function study using FRET-based imaging reveals that PKC␦ binds to and is active at mitochondria via multiple isozyme-specific determinants. Conclusion: Determinants unique to PKC␦ drive an interaction with mitochondria distinct from canonical PKC translocation to membranes. Significance: Isozyme-specific interaction of PKC␦ with mitochondria constitutes a novel recruitment mechanism and increases mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 64 publications
1
32
0
Order By: Relevance
“…17. We cloned Cx43 into the pcDNA3.0 ␦CKAR using a BamHI restriction site and incorporated a 9-amino acid linker consisting of GSAAASFAT between the end of Cx43 and the beginning of the CFP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…17. We cloned Cx43 into the pcDNA3.0 ␦CKAR using a BamHI restriction site and incorporated a 9-amino acid linker consisting of GSAAASFAT between the end of Cx43 and the beginning of the CFP.…”
Section: Methodsmentioning
confidence: 99%
“…Stimulation-The CKAR reporters (nonspecific and ␦CKAR version) have previously been appended to amino acid sequences that target to specific organelles such as mitochondria, the Golgi apparatus, nuclei, and the plasma membrane (15,17,24) as well as to specific proteins such as AKAP79 (25) and PSD95. 3 Here, we appended ␦CKAR to the C terminus of Cx43.…”
Section: The Cx43-␦ckar Biosensor Was Phosphorylated At Ser-368 and Mmentioning
confidence: 99%
“…For instance, Newton and colleagues detected a relatively small but significant PKCδ translocation to the outer mitochondrial membrane (OMM) after the application of a phorbol ester using fluorescence resonance energy (FRET) by generating an OMM-targeted [31] CFP (mt-CFP) and PKCδ-GFP [32]. They also confirmed that PKCδ activity was increased at the OMM upon phorbol-ester stimulation, using the OMM-targeted FRET-based PKCδ kinase activity reporter.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, genetic models showed that PKCβ expression is not necessary for the development of cardiac hypertrophy nor does its absence attenuate the hypertrophic response [30]. PKCε has been suggested to have a protective role in myocardial ischemia-reperfusion injury [31] and arrhythmias [32]. Moreover, the use of specific PKC isoenzyme blockers may lead to novel treatments for heart failure [35; 36] and also for cancers [33] and Alzheimer’s disease [34].…”
Section: Discussionmentioning
confidence: 99%
“…For experiments with forskolin treatment, cells were treated ϳ24 h prior to imaging and transfected the day before. Kinase activity was monitored via intramolecular FRET of the activity reporters (CKAR or CKAR-PB1), and protein translocation was monitored via intermolecular FRET between the YFP-tagged protein and the CFP-tagged target using methods previously described (6,36).…”
Section: Methodsmentioning
confidence: 99%